2015
DOI: 10.1063/1.4914903
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of adsorbed water in MIL-53(Al) by FTIR spectroscopy and ab-initio calculations

Abstract: Here, we report ab-initio calculations developed with a twofold purpose: understand how adsorbed water molecules alter the infrared spectrum of the metal-organic framework MIL-53(Al) and to investigate which are the associated physico-chemical processes. The analyzed structures are the two anhydrous narrow (np⊘) and large (lp⊘) pore forms and the hydrated narrow pore form (np-H2O) of the MIL-53(Al). For these structures, we determined their corresponding infrared spectra (FTIR) and we identified the vibrationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
66
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(70 citation statements)
references
References 77 publications
(84 reference statements)
4
66
0
Order By: Relevance
“…In comparison to the simulated spectrum with data (CCDC numbers: 220 475, 220 476, and 220 477) obtained from the Cambridge Crystallographic Data Centre (CCDC), it is indicated that the as-prepared nanofilm is polycrystalline, whereas an obvious diffractive peak located at the 2θ of 8.3° and a preferential (011) crystalline direction is observed. [42] The peaks distributed from 1250 to 900 cm −1 correspond to the stretching vibration of the SiO bonds in the GaInSn@ PDMS soft electrode. [31] The resultant increasing amount of free space is also essential to accommodate the modifications of the steric hindrance of the MOF constituents during deformation.…”
Section: Wwwadvelectronicmatdementioning
confidence: 99%
“…In comparison to the simulated spectrum with data (CCDC numbers: 220 475, 220 476, and 220 477) obtained from the Cambridge Crystallographic Data Centre (CCDC), it is indicated that the as-prepared nanofilm is polycrystalline, whereas an obvious diffractive peak located at the 2θ of 8.3° and a preferential (011) crystalline direction is observed. [42] The peaks distributed from 1250 to 900 cm −1 correspond to the stretching vibration of the SiO bonds in the GaInSn@ PDMS soft electrode. [31] The resultant increasing amount of free space is also essential to accommodate the modifications of the steric hindrance of the MOF constituents during deformation.…”
Section: Wwwadvelectronicmatdementioning
confidence: 99%
“…68 These predictions were confirmed by subsequent ab initio MD simulations based on density functional theory (DFT). [69][70] More recently, MD simulations were used to reveal the microscopic mechanisms associated with water-mediated proton transport in MIL-53 as a function of temperature, water loading, and pore size. 34 The structure of the hydrated proton was found to resemble that of a distorted Zundel complex when the MIL-53 framework was in the narrow-pore configuration.…”
Section: Introductionmentioning
confidence: 99%
“…A notable case of such stabilization by solvent molecules is the well-known MIL-53, where the narrow pore structure is stabilized by hydrogen bonds between (i) solvent oxygen and hydrogen from the [AlO 4 (OH) 2 ] octahedra, (ii) solvent hydrogen molecules and framework oxygen atoms and (iii) solvent oxygen and solvent hydrogen. 66,67 In these cases, naïve optimization of the solvent-free structure, that fails to adequately consider the effects of temperature and dispersion, will result in a different structure being obtained (the large pore structure for MIL-53). Where geometry optimization produced a structure with any cell parameter deviating by > 20% from the original CoRE structure, we retrieved the original structure from the CCSD to confirm adsorbed molecules as the cause of the deviation and we exclude them from analysis in this work.…”
Section: Breathing and Solvent-stabilized Mofsmentioning
confidence: 99%